Improving Literacy And Numeracy Of Students In Elementary And Junior High School Through Merdeka Belajar Kampus Merdeka (MBKM) - Darwin Lie; Lora Ekana Nainggolan; Nana Triapnita Nainggolan (International Journal Of Community Service, 2022)
Merdeka Belajar-Kampus Merdeka (MBKM) Program aims to be the answer to realizing independent, flexible and quality learning in higher education in order to create an innovative, open and student-oriented learning culture. The MBKM policy relates to higher education learning activities that give students the right and freedom to study outside the program for three semesters which can be used for on-campus and/or extracurricular studies. Kampus Mengajar is part of the MBKM program which aims to provide opportunities for students to learn and personal development through activities outside the classroom. 3th Kampus Mengajar of 2022 will focus on improving literacy and numeracy skills in basic education. This context is getting stronger considering the condition of literacy and numeracy in Indonesia which is still low in line with efforts to increase literacy and numeracy as one of the national priority agendas. The Kampus Mengajar Program opens up space for students to be able to devote their skills and knowledge in helping these elementary and junior high school students. This program also provides opportunities for students to actualize their passion, enthusiasm, and desires.